Peningkatan profesionalitas layanan aparatur desa berbasis e-desa bagi pegawai kantor Desa Rimba Makmur - Nurjayadi Nurjayadi; Torkis Nasution; Herwin Herwin; Khusaeri Andesa (Unri Conference Series: Community Engagement, 2019)
The importance of quality for village employees in the implementation of services and development from the results of the study showed that mental attitude factors, discipline factors, education factors in the field of service will also determine the implementation of tasks for each village government employee. Community service aims to improve the quality of employees and the mastery of technology and information devices at the Village Office staff at Rimba Makmur. Providing insight knowledge about the importance of increasing professionalism in providing services to technology-based society. The target service is all employees, followed by all RT and RW and Kadus. The problem was resolved in three stages of activities namely preparation, implementation and evaluation. Preparations were made by conducting a preliminary survey to see conditions in the field regarding plans to develop information technology and computer-based services. The implementation is carried out with the improvement of hardware and software technology accompanied by training, followed by a discussion of questions and answers and exercises as a form of simulation activities for all services provided by the Village Office. Evaluation of activities is carried out for each stage by collecting and concluding data from each stage of the activity. After the evaluation, the implementation of the implementation of the system directly interacts with the community. In a certain period evaluation is carried out to make improvements continuously. The results of the training activities showed success with an indication of increased satisfaction from internal and community.